Study of Airfoil Deflections for Unsteady Aerodynamics Optimization in Pitching Airfoils - William Refling; Charles Fabijanic; Thomas Sprengeler; Yildirim Bora Suzen; Jordi Estevadeordal (Applied Sciences)
Camber deflection concepts for a VR-12 rotorcraft airfoil were studied for the optimization of unsteady aerodynamics, including dynamic stall conditions and wing–wing interactions during pitching. The designs are based on deflections of the leading edge and trailing edge sections of the airfoil. The deflection parameters were initially established using Computational Fluid Dynamics (CFD). Results from CFD and Particle Image Velocimetry (PIV) were generated for various leading and trailing edge deflection combinations for comparison of their performances. The conditions of this study are for a Reynolds number of 250,000 and pitching reduced frequency of 0.04, representing a medium regime of rotorcraft operations. Linear tandem tests were performed to simulate unsteady wing–wing interactions. The effects of the deflections are discussed and compared to the baseline. Significant benefits are observed, notably dynamic stall mitigation from the leading edge (LE) deflected wing for certain angles of attack and decrease in the separation regions. Overall, from the numerical simulations and the experimental data fields, the LE deflection provides about 10% improvement, followed by the combined LE&TE deflections (8%). It is also found that combining various deflections can provide a performance increase over drastically different areas of the range of angle of attack.